A rotational hybrid energy harvester utilizing bistability for low-frequency applications: Modelling and experimental validation. (15th May 2022) - Xing, Juntong; Fang, Shitong; Fu, Xinlei; Liao, Wei-Hsin
Abstract: Rotational energy harvesting is one of the promising approaches for realizing self-powered wireless sensor networks. Incorporation of hybrid energy sources and geometric bistable nonlinearity can be a solution to enhance the energy harvesting performance under low-frequency excitations. This paper proposes a gravity-based rotational hybrid energy harvester by using the bistable mechanism for low-frequency applications. A comprehensive theoretical model considering the newly introduced piezoelectric stack and force magnification frame is derived for the first time based on the extended Hamilton's principle. The piezoelectric and electromagnetic coupling coefficients are explicitly expressed and analysed. Both numerical and experimental results show that increasing the spring stiffness can amplify the harvested energy at a higher excitation frequency, and narrowing the impact gap can broaden the effective working bandwidth. Furthermore, the maximum power usually occurs with the impact inter-well phenomenon, after which the chaotic and intra-well oscillations appear successively. Besides, the maximum total power output of 2.98 mW is generated at 7.5 Hz with spring stiffness of 4200 N m −1, which is at least one order of magnitude higher than the other state-of-the-art energy harvesters under the same excitation. Based on the validated theoretical model, parametric studies are further performed to investigate the effects of the proof mass and the initial prestress on the piezoelectric stack. It is found that the hybrid rotational energy harvesting system can possess high tunability and adaptability to the frequency-variant environment by adjusting multiple structural parameters. Graphical abstract: Highlights: A rotational bistable hybrid energy harvester is proposed for low-frequency scenarios. The electromechanical model is established comprehensively. Experiments are conducted to validate the derived model. Parametric studies are performed to study the influences of structural parameters. Performance is evaluated by comparing with state-of-the-art energy harvesters.